THE EFFECT OF GROSS REGIONAL DOMESTIC PRODUCT (GRDP) AND MUNICIPAL MINIMUM WAGE (MMW) ON THE OPEN UNEMPLOYMENT RATE ACROSS REGENCIES/CITIES IN BALI - Nabilil Wildan Nuril Anwar; Ida Bagus Putu Purbadharmaja (Adisam Publisher, 2026)
Unemployment remains a persistent economic issue in regional development, including in Bali Province. The Open Unemployment Rate (OUR) reflects imbalances between labor supply and labor demand, which are influenced by regional economic performance and labor market policies. This study examines the effects of Gross Regional Domestic Product (GRDP) and the Regency/Municipality Minimum Wage (RMW) on the Open Unemployment Rate across regencies and municipalities in Bali Province. This study employs a quantitative approach using panel data from nine regencies and municipalities in Bali Province over the period 2019–2023. Secondary data were obtained from the Bali Provincial Statistics Office (BPS) and analyzed using panel data regression. Model selection was conducted using the Chow test and the Hausman test. The results indicate that GRDP has a negative and statistically significant effect on the Open Unemployment Rate, indicating that higher regional economic output is associated with lower unemployment. In contrast, the minimum wage has a positive and statistically significant effect on the Open Unemployment Rate, suggesting a potential reduction in labor demand. Simultaneously, GRDP and the minimum wage jointly have a significant effect on the Open Unemployment Rate across regencies and municipalities in Bali Province.